2023
DOI: 10.1038/s41467-023-36434-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of chaos in a compartmentalized catalytic reaction nanosystem

Abstract: In compartmentalized systems, chemical reactions may proceed in differing ways even in adjacent compartments. In compartmentalized nanosystems, the reaction behaviour may deviate from that observed on the macro- or mesoscale. In situ studies of processes in such nanosystems meet severe experimental challenges, often leaving the field to theoretical simulations. Here, a rhodium nanocrystal surface consisting of different nm-sized nanofacets is used as a model of a compartmentalized reaction nanosystem. Using fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Above all, on this volcano-like dependence curve of apparent activity on La coverage, activity on the left leg is limited by the La coverage, whereas that on the right leg is hampered by the insufficient number of Co B 5 sites. A medium coverage of La as a promotor on a rhodium (Rh) surface for an optimized performance toward hydrogen oxidation reaction was reported recently (26).…”
Section: Experimental Verification On Model Catalyst Of Co Single Cry...mentioning
confidence: 99%
“…Above all, on this volcano-like dependence curve of apparent activity on La coverage, activity on the left leg is limited by the La coverage, whereas that on the right leg is hampered by the insufficient number of Co B 5 sites. A medium coverage of La as a promotor on a rhodium (Rh) surface for an optimized performance toward hydrogen oxidation reaction was reported recently (26).…”
Section: Experimental Verification On Model Catalyst Of Co Single Cry...mentioning
confidence: 99%
“…XPEEM alone can already provide correlative spectroscopic data and microscopy images, but its capabilities are limited in terms of spectroscopy of sub-micrometer areas and imaging areas larger than several micrometers. , Thus, a combination with other techniques is often beneficial. Apart from the known steady states of high and low activity and bistability, previous studies shed light on the spatio-temporal phenomena in catalytic H 2 oxidation on Rh, including mono- and multi-frequential self-sustaining oscillations, ,, coexisting multi-states, or the emergence of chaos . For supported Rh particles, such an approach has not yet been applied.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the known steady states of high and low activity and bistability, 41 44 previous studies shed light on the spatio-temporal phenomena in catalytic H 2 oxidation on Rh, including mono- and multi-frequential self-sustaining oscillations, 12 , 45 , 46 coexisting multi-states, 47 or the emergence of chaos. 48 For supported Rh particles, such an approach has not yet been applied. Based on the thorough understanding of the mechanism of hydrogen oxidation, it can be used as a test reaction to probe catalytically inactive and active states.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] Chaos, which is an important development of nonlinear time series analysis, has been widely found in biology, [ 20,21 ] medicine, [ 22 ] finance, [ 23 ] industrial, [ 24,25 ] and other research areas. [ 26–28 ] It has been confirmed that chaotic phenomena exist not only in the aforementioned kinds of systems, but also in various fluids mixing systems. For instance, Ghayesh et al studied the effect of flow pulsations on chaos in nanotubes using nonlocal strain gradient theory.…”
Section: Introductionmentioning
confidence: 99%